LITERATURE REVIEW: IMPROVING THE PROFESSIONALISM OF GUIDANCE AND COUNSELING TEACHERS IN SCHOOLS THROUGH GUIDANCE AND COUNSELING SUPERVISION - Kharisma Amelia Putri; Nandang Budiman; Nadia Aulia Nadhirah (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2024)
Guidance and counseling supervision is an effort to evaluate the performance of guidance and counseling teachers, so that they are able to understand and master the skills needed to provide guidance and counseling services. The role of supervision is needed to help guidance and counseling teachers become professional individuals so that they are able to manage counseling service delivery programs in schools well. This research aims to determine the importance of guidance and counseling supervision in increasing the professionalism of guidance and counseling teachers in schools. The research method used is through a systematic literature review (SLR) approach. Data collection techniques are carried out by collecting information from relevant sources such as books, journals, research results and e-books that are appropriate to the problem being discussed so that research data can be clarified. The research results concluded that the implementation of guidance and counseling supervision in schools was able to significantly increase the professionalism of guidance and counseling teachers so that quality counseling services could be created.